Synergistic Effect of Antibiotic Fucidic acid with Cinnamomum zeylanicum and Curcuma longa Extracts against Escherichia coli and Staphylococcus aureus - Risan, Mohsen Hashem (International Journal of Pharmaceutical & Biological Archive, 2022)
The present study focused on evaluation of antibacterial effect of Cinnamomum zeylanicum and Curcuma longa extracts and their synergistic effect with some antibiotic. Antimicrobial activity of plant extracts against Escherichia coli. C. longa was showed the highest effect against E. coli with a zone of inhibition 13 and 14.5 mm at a concentration of 100 and 200 mg/mL, respectively. While antimicrobial activity was observed by C. zeylanicum, with a zone of inhibition 9 and 13.9 mm at a concentration of 100 and 200 mg/mL, respectively. Antimicrobial activity against Staphylococcus aureus with a zone of inhibition 11 and 16.8 mm at a concentration of 100 and 200 mg/mL, respectively, of C. longa. No antimicrobial activity was observed by C. zeylanicum, at a concentration of 100 mg/mL and a zone of inhibition 10 mm at a concentration of 200 mg/mL, antibiotics activity of Fucidic acid (50 mg, 100 mg) against S. aureus and E. coli. Fucidic acid was showed effectiveness against S. aureus and E. coli with a zone of inhibition 15 and 17 mm at a concentration of 50 mg, respectively. While was zone of inhibition 17.4 and 19 mm at a concentration of 100 mg against S. aureus and E. coli, respectively. Extract of C. zeylanicum increased the effectiveness of Fucidic acid against E. coli (17 mm). As for the C. longa extract was the results with Fucidic acid on the bacteria (22 mm). C. zeylanicum and C. longa extracts and antibiotics, extract of Cinnamomum Zeylanicum increased the effectiveness each of Fucidic acid against S. aureus (18.6 mm). As for the C. longa extract was the results (when added to antibiotics) almost similar to C. zeylanicum extract, where it also has increased the impact of Fucidic acid on the bacteria S. aureus (20.4 mm).